2017
DOI: 10.28925/2312-5829.2017.3-4.3932
|View full text |Cite
|
Sign up to set email alerts
|

Vr-Technology as a Method and Means of Training

Abstract: У статті звернено увагу на один з перспективних освітніх методів, запропонованих сучасними інформаційними технологіями,віртуальну реальність, яка моделюється комп'ютером. Реальних досліджень віртуальної реальності в педагогіці здійснюється вкрай мало. Автори наявних праць зводять застосування технологій віртуальної освіти до використання електронних підручників і тестових оболонок, рідше мультимедійних матеріалів, в окремих випадкахкомп'ютерних віртуальних симуляторів і тренажерів. Відтак, мета даної статті уз… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Huang, C. Ball, J. Francis, R. Ratan, J. Bowmis, J. Ford ham [5], J. Johnson [6], V. Klimnyuk [7], Yu. Trach [8], and others. R.L.S.…”
Section: Technologies That Expand Realitymentioning
confidence: 98%
See 1 more Smart Citation
“…Huang, C. Ball, J. Francis, R. Ratan, J. Bowmis, J. Ford ham [5], J. Johnson [6], V. Klimnyuk [7], Yu. Trach [8], and others. R.L.S.…”
Section: Technologies That Expand Realitymentioning
confidence: 98%
“…First of all, let us talk about the advantages of using immersive technologies in research and edu cation: their visibility, security, opportunities to attract and to focus audience [8], relative afforda bility, and cognitive potential. In particular, experts from the Fluid Interfaces Group of the MIT Media Lab (Massachusetts Institute of Technology) ha ve found that with augmented reality technology, the accuracy of longterm retention of a sequence of objects in memory is tripled as compared with the memorizing information from paper [20].…”
Section: Extended Reality For Scholarly Researchmentioning
confidence: 99%
“…A distinctive feature of this environment is the change of images in real time and the experience of the effect of presence. VR simulates both the impact and the response to that effect [7].…”
mentioning
confidence: 99%
“…Virtual reality technologies give the opportunity to use fully that a person receives 80% of information from the outside world through vision, herewith people remember 20% of what they see, 40% of what they see and hear, and 70% of what they see, hear and do. As a result, students are fully involved in the learning process that increases motivation and success in gaining knowledge [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation